Viotá: pedagogical possibilities of a reborn paradise - Chaves Remolina, Andrés Mauricio; Piraquive Monroy, Diana Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Viotá has been a scene of ideological struggles and of an extended process of violence characteristic of the armed conflict in Colombia that has affected the internal dynamics of the municipality, particularly the relationships between its people and their sense of belonging. In this context the subproject ‘Identity and Cultural Heritage’ —assigned to the project ‘Design, implementation, management and projection of Research and Development (R &amp, D) of the pilot program for the creation of productive projects in Central and West Cundinamarca, epicenter Viotá: Potentiating the City-region’, by the Universidad Piloto de Colombia— proposed to generate, in 2014, teaching strategies from historical and cultural approaches in order to strengthen the collective identity, specifically articulated with two schools in the municipality. In this perspective, some methodological details are presented and the teaching strategy —formulated on the basis of the community’s needs— is explained.